Enhanced multistress tolerance of Saccharomyces cerevisiae with the sugar transporter-like protein Stl1F427L mutation in the presence of glycerol - Zixiong Liu; Lingling Shangguan; Linglong Xu; Huiyan Zhang; Wenxin Wang; Qiao Yang; Xiaoling Zhang; Lan Yao; Shihui Yang; Xiong Chen; Jun Dai (Microbiology Spectrum)
ABSTRACT During microbial industrial production, microorganisms often face diverse stressors, including organic solvents, high salinity, and high sugar levels. Enhancing microorganism tolerance to such stresses is crucial for producing high-value-added products. Previous studies on the mechanisms of 2-phenylethanol (2-PE) tolerance in Saccharomyces cerevisiae revealed a potential connection between the sugar transporter-like protein (Stl1) mutation (F427L) and increased tolerance to high sugar and salt stress, suggesting a broader role in multistress tolerance. Herein, we showed that the Stl1F427L mutant strain (STL) exhibits significantly improved multistress tolerance in the presence of glycerol. Molecular dynamics simulations indicated that Stl1F427L may enhance glycerol molecular binding, resulting in a significant increase in the intracellular glycerol content of the mutant strain STL. Additionally, under multistress conditions, pyruvate and ergosterol levels and catalase (CAT) and superoxide dismutase (SOD) activities were significantly increased in the mutant strain STL compared with the control strain 5D. This resulted in a notable increase in cell membrane toughness and a decrease in intracellular reactive oxygen species levels. These findings highlight the mechanism by which Stl1F427L enhances S. cerevisiae tolerance to multistress. Importantly, they provide novel insights into and methodologies for improving the resilience of industrial microorganisms.IMPORTANCEStl1F427L exhibits improved strain tolerance to multistress when adding glycerol, may enhance glycerol molecular binding, and can make a significant increase in intracellular glycerol content. It can reduce reactive oxygen species levels and increase ergosterol content. This paper provides novel insights and methods to get robust industrial microorganisms.